(untitled) (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2015)
The purpose of the study is to reflect on the research process at the Faculty of Economics of the National Autonomous University of Nicaragua. Statistical information was collected using a questionnaire to a sample of teachers from different schools working full time during 1999. It has been found that the research process is not simple and you can not make generalizations about the lack of a research culture in the faculty of economics. At most we can assert that research is fragmented and irrelevant in some cases. Therefore, it is necessary to rebuild our investigative research teaching work towards strengthening an instance or entity that organizes the research process together with an incentive scheme for research. A platform is required in the form of seminars and forums that enable teachers to evacuate their ideas on the subject of research to create internal synergy. The research mode via the monograph is key to the process, however, the mode of monographs as a form of scientific work must be related to a line of research. DOI: http://dx.doi.org/10.5377/reice.v2i4.1727 REICE Vol. 2, No. 4, julio-diciembre 2014: 70-95